Can Public Housing Decrease Segregation? Lessons and Challenges from Non-European Immigration in France - Gregory Verdugo; Sorana Toma (Institute of Labor Economics (IZA), 2018)
Recent decades have seen a rapid increase in the share of non-European immigrants in public housing in Europe, which has led to concern regarding the rise of "ghettos" in large cities. Using French census data over three decades, we examine how this increase in public housing participation has affected segregation. While segregation levels have increased moderately on average, the number of immigrant enclaves has grown. The growth of enclaves is being driven by the large increase in non-European immigrants in the census tracts where the largest housing projects are located, both in the housing projects and the surrounding non-public dwellings. As a result, contemporary differences in segregation levels across metropolitan areas are being shaped by the concentration of public housing within cities, in particular the share of non-European immigrants in large housing projects constructed before the 1980s. Nevertheless, the overall effect of public housing on segregation has been ambiguous. While large projects have increased segregation, the inflows of non-European immigrants into small projects have brought many immigrants into census tracts where they have previously been rare and, thus, diminished segregation levels.
Keywords: J15; R31; 330; immigration; social housing; public housing; segregation; Europe; France